Cultural Differences in Opportunity Cost Consideration - Zhang, Ning; Ji, Li-Jun; Li, Ye (Frontiers in Psychology, 2017)
Two studies were conducted to investigate cultural differences in opportunity cost consideration between Chinese and Euro-Canadians. Opportunity cost is defined as the cost of a benefit that must be forgone in order to pursue a better alternative (Becker, Ronen, & Sorter, 1974). In both studies, participants read about hypothetical purchase scenarios, and then decided whether they would buy a certain product. Opportunity cost consideration was measured in two ways: (1) participants’ thoughts pertaining to other (nonfocal) products while making decisions; (2) participants’ decisions not to buy a focal product (Study 1) or a more expensive product (Study 2). Across both indexes, we found that after controlling for individual difference variables and amount of pocket money, Chinese participants in China considered financial opportunity cost more than Euro-Canadians in Study 1. Similar results were observed in Study 2 when comparing Chinese in Canada with Euro-Canadians However, the cultural effect on opportunity cost consideration was confounded by family income in Study 2. Implications for resource management, limitations of the current research and directions for future research are discussed.